The correlation between Smac, IAPs and mitochondrial apoptosis, muscle tenderness during postmortem aging of Oula Tibetan sheep meat - Jingyu Wang; Ruina Zhao; Yang Liu; Tieying Hu; Xiaolong Li; Long He; Zhaobin Guo; Cheng Chen; Xixiong Shi (Food Chemistry: X)
Oula Tibetan sheep meat has rich nutritional value but relatively poor tenderness. Recently, apoptosis of muscle cells has gradually become a research hotspot for improving meat tenderness during postmortem aging. Smac can promote the decrease of IAPs expression in tumor cells, thereby inducing mitochondrial apoptosis. However, the relationship between Smac, IAPs and mitochondrial apoptosis, muscle tenderness during postmortem meat aging is still unclear. Thus, the aim of this work was to explore the relationship between Smac, IAPs and mitochondrial apoptosis as well as muscle tenderness during postmortem meat aging. Smac concentration, IAPs concentration, pH value, ATP content, SDH activity, MPTP opening degree, MMP, caspase-3/9 activity, apoptotic rate, MFI and shear force value of Oula Tibetan sheep meat were measured at different aging times and correlation analysis was performed. Correlation analysis revealed that Smac, IAPs were markedly related to mitochondrial apoptosis and muscle tenderness during postmortem aging of Tibetan sheep meat. The results suggest that Smac may regulate IAPs to promote mitochondrial apoptosis and muscle tenderization in Oula Tibetan sheep meat during postmortem aging.